The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/biomedicines9121905
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pharmacological Inhibition of the Activity of All NOS Isoforms Rather Than Genetic Knock-Out of Endothelial NOS Leads to Impaired Spatial Learning and Memory in C57BL/6 Mice

Abstract: Increasing epidemiological and experimental evidence points to a link between arterial stiffness and rapid cognitive decline. However, the underlying mechanism linking the two diseases is still unknown. The importance of nitric oxide synthases in both diseases is well-defined. In this study, we introduced arterial stiffness in both genetic (eNOS−/−, endothelial nitric oxide synthase knockout) and pharmacological (N(G)-nitro-L-arginine methyl ester (L-NAME) treatment) NO dysfunction models to study their associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 46 publications
0
9
1
Order By: Relevance
“…As expected, we found significantly increased PWV values in L-NAME-treated animals compared to controls after 2, 8, and 16 weeks of treatment, which was progressively significant over time. Moreover, we found that long-term L-NAME treatment led to impaired visuospatial learning and memory [ 21 ]. The goal of this study was to further explore the observed progressive cognitive decline because of L-NAME treatment via proteomic analysis of hippocampal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As expected, we found significantly increased PWV values in L-NAME-treated animals compared to controls after 2, 8, and 16 weeks of treatment, which was progressively significant over time. Moreover, we found that long-term L-NAME treatment led to impaired visuospatial learning and memory [ 21 ]. The goal of this study was to further explore the observed progressive cognitive decline because of L-NAME treatment via proteomic analysis of hippocampal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…After sixteen weeks of NOS inhibition with L-NAME and the point reached of significantly deteriorated visuospatial learning and memory of treated C57BL/6 mice [ 21 ], 120 DEPs were found in their hippocampi. In accordance with our findings of 2-week L-NAME-treated hippocampi, we observed the downregulation of the Gabbr2, GABA B receptor subunit 2, alongside a downregulation of Sfn, 14-3-3 protein sigma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations